Composite material for shoe upper and preparation method thereof
By using composite materials with specific ratios in the upper material, including styrene butadiene rubber, butadiene rubber and functional additives, the lack of breathability, wear resistance and fold stability of existing materials is solved, and the temperature is achieved. Effective temperature control effect improves the overall performance of the product.
Patent Information
- Application Number
- CN202411533331.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-31
AI Technical Summary
The existing upper materials have shortcomings in breathability, wear resistance and fold stability, and are difficult to achieve temperature control effects, which limits the efficiency of the product.
Using a composite material, including styrene butadiene rubber, butadiene rubber, EVA, bidirectional agent for edge adjustment, chitosan modifier, zinc oxide, stearic acid, carbon black and sulfur, through specific raw materials proportioning and treatment Methods: improve the breathability, wear resistance and fold stability of the material, and achieve the temperature control effect.
The breathable and wear resistance of the upper material is significantly improved, the folding stability of the product is improved, and the excellent temperature control effect is achieved, and the temperature is controlled within the range of 24℃~28℃.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of shoe upper materials, and in particular to a composite material for shoe uppers and a preparation method thereof. Background Art
[0002] At present, the main materials used for plastic uppers are rubber, thermoplastic elastomers and plastics, and the performance of uppers made of various materials is different; the existing upper materials have poor air permeability and wear resistance, and the product has poor folding stability. At the same time, it is difficult for the product to achieve temperature control effects, which limits the efficiency of product use. Summary of the invention
[0003] In view of the defects of the prior art, the purpose of the present invention is to provide a composite material for a shoe upper and a preparation method thereof, so as to solve the problems raised in the above background technology.
[0004] The present invention solves the technical problem by adopting the following technical solution:
[0005] The present invention provides a composite material for a shoe upper, comprising the following raw materials in parts by weight:
[0006] 35-45 parts of styrene-butadiene rubber, 35-40 parts of butadiene rubber, 10-15 parts of EVA, 8-14 parts of edge-adjusting functional bidirectional agent, 5-8 parts of chitosan modifier, 4-6 parts of zinc oxide, 2-4 parts of stearic acid, 2-4 parts of carbon black, 2-3 parts of sulfur, and 2-3 parts of vulcanization accelerator TMTM.
[0007] Preferably, the composite material for the upper comprises the following raw materials in parts by weight:
[0008] 40 parts of styrene-butadiene rubber, 37.5 parts of butadiene rubber, 12.5 parts of EVA, 11 parts of edge-adjusting functional bidirectional agent, 6.5 parts of chitosan modifier, 5 parts of zinc oxide, 3 parts of stearic acid, 3 parts of carbon black, 2.5 parts of sulfur, and 2.5 parts of vulcanization accelerator TMTM.
[0009] Preferably, the preparation method of the side-adjusting functional bidirectional agent is:
[0010] S01: The nano-bentonite is first heat-treated at 300-320°C for 5-10 minutes, then cooled to 170°C at a rate of 2-4°C / min, kept warm for 5 minutes, and finally air-cooled to room temperature to obtain the heat-treated nano-bentonite;
[0011] S02: first prepare a phosphate buffer solution with a pH value of 5.0-5.5, then add 1-3 parts of silane coupling agent KH560 and 1-2 parts of sodium dodecylbenzene sulfonate solution to 4-7 parts of the phosphate buffer solution, and then add 2-4 parts of carboxymethyl cellulose and mix well to obtain a modified solution;
[0012] S03: stirring the heat-treated nano-bentonite and the modified liquid at a weight ratio of 2:5 for modification, washing with water and drying after the stirring is completed to obtain modified nano-bentonite;
[0013] S04: The modified nano-bentonite and the edge-adjusting agent are mixed and ball-milled in a weight ratio of 5:3 at a ball-milling speed of 1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain an edge-adjusting functional bidirectional agent.
[0014] Preferably, the stirring speed of the stirring modification treatment is 550-750 r / min, and the stirring time is 20-30 min.
[0015] Preferably, the mass fraction of the sodium dodecylbenzene sulfonate solution is 2-5%.
[0016] Preferably, the edge adjuster comprises the following raw materials in parts by weight:
[0017] 2~4 parts of silicon carbide whiskers, 1~3 parts of nano-silica sol, 4~7 parts of sodium alginate solution, 2~4 parts of lanthanum chloride solution and 1~3 parts of nano-silicon dioxide.
[0018] Preferably, the mass fraction of the sodium alginate solution is 4-6%; the mass fraction of the lanthanum chloride solution is 3-5%.
[0019] The inventors of the present invention found that when silicon carbide whiskers were not added to the edge conditioner, the performance of the product deteriorated most significantly among the preparation factors of the edge conditioner, followed by the failure to add nano-silicon dioxide. At the same time, when lanthanum chloride solution, nano-silica sol and sodium alginate solution were not added, the performance of the product tended to deteriorate. Only when the specific raw materials of the present invention were used, the performance effect of the product was the most significant. The technical effect of the present invention could not be achieved by using other raw materials instead.
[0020] Preferably, the preparation method of the chitosan modifier is:
[0021] S11: irradiating the yttrium oxide in a proton irradiation box for 5-10 minutes at an irradiation power of 350-400W, and obtaining irradiated yttrium oxide after the irradiation is completed;
[0022] S12: 2-5 parts of irradiated yttrium oxide, 3-6 parts of chitosan solution, 1-3 parts of silane coupling agent KH550 and 1-2 parts of urea are mixed and ball-milled thoroughly at a ball-milling speed of 1000-1500 r / min. After the ball-milling is completed, the mixture is filtered and dried to obtain a chitosan modifier.
[0023] Preferably, the mass fraction of the chitosan solution is 2-5%.
[0024] The present invention also provides a method for preparing a composite material for a shoe upper, comprising the following steps:
[0025] The raw materials are weighed according to weight, and then styrene-butadiene rubber, butadiene rubber, EVA, edge adjustment functional bidirectional agent, chitosan modifier, zinc oxide, stearic acid and carbon black are first kneaded at a temperature of 165-175°C for 5 minutes, and then sulfur and vulcanization accelerator TMTM are added and kneaded at a temperature of 40°C for 35-45 minutes. After the kneading is completed, a composite material for shoe uppers is obtained.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. The composite material for the upper of the present invention adopts styrene-butadiene rubber, butadiene rubber and EVA as the matrix material, and zinc oxide, stearic acid, carbon black, sulfur and vulcanization accelerator TMTM are added as functional additives, and the edge adjustment functional bidirectional agent and chitosan modifier are matched. Through the mutual matching of the raw materials, the air permeability and wear resistance of the product are improved in an integrated manner, and the folding stability of the product is remarkable. At the same time, the product can achieve excellent temperature control effect, and the product temperature is controlled at 24°C~28°C;
[0028] 2. The nano-bentonite is first heat-treated at 300-320°C for 5-10 minutes as the functional bidirectional agent, then cooled to 170°C at a rate of 2-4°C / min, kept warm for 5 minutes, and finally air-cooled to room temperature to obtain the heat-treated nano-bentonite. Through multi-stage thermal improvement, the active efficiency of the nano-bentonite is optimized, the interlayer spacing of the nano-bentonite is improved, the temperature adjustment efficiency of the nano-bentonite and the interlayer permeability are improved, and the silane coupling agent KH560, sodium dodecylbenzene sulfonate solution, phosphate buffer solution and carboxymethyl The cellulose is blended to obtain a modified liquid. The silane coupling agent KH560 in the modified liquid has an interface improvement effect, and the sodium dodecylbenzene sulfonate solution improves the activity efficiency between the raw materials. At the same time, the acidic activity of the phosphate buffer solution and the addition of carboxymethyl cellulose jointly optimize the mutual enhancement effect between the raw materials. The raw materials in the modified liquid are matched and assisted with each other, so that the modified liquid can better improve the activity and dispersibility of the nano-bentonite, optimize the improvement effect of the nano-bentonite on the edge adjustment, and thus improve the performance efficiency of the product;
[0029] 3. The edge adjuster uses silicon carbide whiskers as the matrix, and silicon carbide whiskers are matched with bentonite. Silicon carbide whiskers have a whisker-like structure, while bentonite has a lamellar structure. In terms of space, the whiskers and lamellar structures are matched with each other to improve the spatial compactness, thereby improving the coordinated improvement of product performance, and harmonizing and matching nano-silica sol, sodium alginate solution, lanthanum chloride solution and nano-silica. The sodium alginate solution in the edge adjuster is the matrix medium to enhance the dispersibility between the raw materials, and the rare earth lanthanum chloride solution is matched with nano-silica sol to enhance the coordination and coordination between nano-silica and silicon carbide whiskers. Silicon carbide whiskers are matched with nano-silica with a whisker-like structure and a high specific surface area to enhance the dispersibility of the system interface, and the high specific surface area nano-silica is matched with silicon carbide whiskers to synergistically improve the air permeability and wear resistance of the product, and optimize the folding stability of the product and the excellent temperature control effect of the product;
[0030] 4. The chitosan modifier uses yttrium oxide to be irradiated with protons to stimulate the activity of yttrium oxide, and then the chitosan solution, silane coupling agent KH550 and urea are fully blended and ball-milled. Through the mutual assistance between the raw materials, the chitosan solution in the system enhances the compatibility between the raw materials in the system. At the same time, the silane coupling agent, as an interface additive, cooperates with urea to enhance the permeability of the raw materials. Therefore, through the mutual adjustment and complementarity of the raw materials in the chitosan modifier, the coordination effect of the chitosan modifier and the side-adjusting functional bidirectional agent is further enhanced, and the performance of the product is further improved. DETAILED DESCRIPTION
[0031] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] An embodiment of the present invention provides a composite material for a shoe upper, comprising the following raw materials in parts by weight:
[0033] 35-45 parts of styrene-butadiene rubber, 35-40 parts of butadiene rubber, 10-15 parts of EVA, 8-14 parts of edge-adjusting functional bidirectional agent, 5-8 parts of chitosan modifier, 4-6 parts of zinc oxide, 2-4 parts of stearic acid, 2-4 parts of carbon black, 2-3 parts of sulfur, and 2-3 parts of vulcanization accelerator TMTM.
[0034] The preparation method of the bidirectional agent with side-modulating function in this embodiment is as follows:
[0035] S01: The nano-bentonite is first heat-treated at 300-320°C for 5-10 minutes, then cooled to 170°C at a rate of 2-4°C / min, kept warm for 5 minutes, and finally air-cooled to room temperature to obtain the heat-treated nano-bentonite;
[0036] S02: first prepare a phosphate buffer solution with a pH value of 5.0-5.5, then add 1-3 parts of silane coupling agent KH560 and 1-2 parts of sodium dodecylbenzene sulfonate solution to 4-7 parts of the phosphate buffer solution, and then add 2-4 parts of carboxymethyl cellulose and mix well to obtain a modified solution;
[0037] S03: stirring the heat-treated nano-bentonite and the modified liquid at a weight ratio of 2:5 for modification, washing with water and drying after the stirring is completed to obtain modified nano-bentonite;
[0038] S04: The modified nano-bentonite and the edge-adjusting agent are mixed and ball-milled in a weight ratio of 5:3 at a ball-milling speed of 1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain an edge-adjusting functional bidirectional agent.
[0039] The stirring speed of the stirring modification treatment in this embodiment is 550-750 r / min, and the stirring time is 20-30 min.
[0040] The mass fraction of the sodium dodecylbenzene sulfonate solution in this embodiment is 2-5%.
[0041] The side conditioning agent in this embodiment includes the following raw materials in parts by weight:
[0042] 2~4 parts of silicon carbide whiskers, 1~3 parts of nano-silica sol, 4~7 parts of sodium alginate solution, 2~4 parts of lanthanum chloride solution and 1~3 parts of nano-silicon dioxide.
[0043] The mass fraction of the sodium alginate solution in this embodiment is 4-6%; the mass fraction of the lanthanum chloride solution is 3-5%.
[0044] The preparation method of the chitosan modifier in this embodiment is:
[0045] S11: irradiating the yttrium oxide in a proton irradiation box for 5-10 minutes at an irradiation power of 350-400W, and obtaining irradiated yttrium oxide after the irradiation is completed;
[0046] S12: 2-5 parts of irradiated yttrium oxide, 3-6 parts of chitosan solution, 1-3 parts of silane coupling agent KH550 and 1-2 parts of urea are mixed and ball-milled thoroughly at a ball-milling speed of 1000-1500 r / min. After the ball-milling is completed, the mixture is filtered and dried to obtain a chitosan modifier.
[0047] The mass fraction of the chitosan solution in this embodiment is 2-5%.
[0048] This embodiment also provides a method for preparing a composite material for a shoe upper, comprising the following steps:
[0049] The raw materials are weighed according to weight, and then styrene-butadiene rubber, butadiene rubber, EVA, edge adjustment functional bidirectional agent, chitosan modifier, zinc oxide, stearic acid and carbon black are first kneaded at a temperature of 165-175°C for 5 minutes, and then sulfur and vulcanization accelerator TMTM are added and kneaded at a temperature of 40°C for 35-45 minutes. After the kneading is completed, a composite material for shoe uppers is obtained.
[0050] Embodiment 1: A composite material for a shoe upper, comprising the following raw materials in parts by weight:
[0051] 35 parts of styrene-butadiene rubber, 35 parts of butadiene rubber, 10 parts of EVA, 8 parts of edge-adjusting functional bidirectional agent, 5 parts of chitosan modifier, 4 parts of zinc oxide, 2 parts of stearic acid, 2 parts of carbon black, 2 parts of sulfur, and 2 parts of vulcanization accelerator TMTM.
[0052] The preparation method of the bidirectional agent with side-modulating function in this embodiment is as follows:
[0053] S01: The nano-bentonite is first heat-treated at 300°C for 5 minutes, then cooled to 170°C at a rate of 2°C / min, kept warm for 5 minutes, and finally air-cooled to room temperature to obtain the heat-treated nano-bentonite;
[0054] S02: First prepare a phosphate buffer solution with a pH value of 5.0, then add 1 part of silane coupling agent KH560 and 1 part of sodium dodecylbenzene sulfonate solution to 4 parts of the phosphate buffer solution, and then add 2 parts of carboxymethyl cellulose and mix well to obtain a modified solution;
[0055] S03: stirring the heat-treated nano-bentonite and the modified liquid at a weight ratio of 2:5 for modification, washing with water and drying after the stirring is completed to obtain modified nano-bentonite;
[0056] S04: The modified nano-bentonite and the edge-adjusting agent are mixed and ball-milled in a weight ratio of 5:3 at a ball-milling speed of 1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain an edge-adjusting functional bidirectional agent.
[0057] The stirring speed of the stirring modification treatment in this embodiment is 550 r / min, and the stirring time is 20 min.
[0058] The mass fraction of the sodium dodecylbenzene sulfonate solution in this embodiment is 2%.
[0059] The side conditioning agent in this embodiment includes the following raw materials in parts by weight:
[0060] 2 parts of silicon carbide whiskers, 1 part of nano-silica sol, 4 parts of sodium alginate solution, 2 parts of lanthanum chloride solution and 1 part of nano-silicon dioxide.
[0061] The mass fraction of the sodium alginate solution in this embodiment is 4%; the mass fraction of the lanthanum chloride solution is 3%.
[0062] The preparation method of the chitosan modifier in this embodiment is:
[0063] S11: irradiating the yttrium oxide in a proton irradiation box for 5 minutes at an irradiation power of 350 W, and obtaining irradiated yttrium oxide after the irradiation is completed;
[0064] S12: 2 parts of irradiated yttrium oxide, 3 parts of chitosan solution, 1 part of silane coupling agent KH550 and 1 part of urea are mixed and ball-milled thoroughly at a ball-milling speed of 1000 r / min. After the ball-milling is completed, the mixture is filtered and dried to obtain a chitosan modifier.
[0065] The mass fraction of the chitosan solution in this embodiment is 2%.
[0066] This embodiment also provides a method for preparing a composite material for a shoe upper, comprising the following steps:
[0067] The raw materials were weighed according to their weight, and then styrene-butadiene rubber, butadiene rubber, EVA, edge adjustment functional bidirectional agent, chitosan modifier, zinc oxide, stearic acid and carbon black were first kneaded at a temperature of 165°C for 5 minutes, and then sulfur and vulcanization accelerator TMTM were added and kneaded at a temperature of 40°C for 35 minutes. After the kneading was completed, a composite material for shoe uppers was obtained.
[0068] Embodiment 2: A composite material for a shoe upper, comprising the following raw materials in parts by weight:
[0069] 45 parts of styrene-butadiene rubber, 40 parts of butadiene rubber, 15 parts of EVA, 14 parts of edge-adjusting functional bidirectional agent, 8 parts of chitosan modifier, 6 parts of zinc oxide, 4 parts of stearic acid, 4 parts of carbon black, 3 parts of sulfur, and 3 parts of vulcanization accelerator TMTM.
[0070] The preparation method of the bidirectional agent with side-modulating function in this embodiment is as follows:
[0071] S01: The nano-bentonite was first heat-treated at 320°C for 10 min, then cooled to 170°C at a rate of 4°C / min, kept warm for 5 min, and finally air-cooled to room temperature to obtain the heat-treated nano-bentonite;
[0072] S02: first prepare a phosphate buffer solution with a pH value of 5.5, then add 3 parts of silane coupling agent KH560 and 2 parts of sodium dodecylbenzene sulfonate solution to 7 parts of the phosphate buffer solution, and then add 4 parts of carboxymethyl cellulose and mix well to obtain a modified solution;
[0073] S03: stirring the heat-treated nano-bentonite and the modified liquid at a weight ratio of 2:5 for modification, washing with water and drying after the stirring is completed to obtain modified nano-bentonite;
[0074] S04: The modified nano-bentonite and the edge-adjusting agent are mixed and ball-milled in a weight ratio of 5:3 at a ball-milling speed of 1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain an edge-adjusting functional bidirectional agent.
[0075] The stirring speed of the stirring modification treatment in this embodiment is 750 r / min, and the stirring time is 30 min.
[0076] The mass fraction of the sodium dodecylbenzene sulfonate solution in this embodiment is 5%.
[0077] The side conditioning agent in this embodiment includes the following raw materials in parts by weight:
[0078] 4 parts of silicon carbide whiskers, 3 parts of nano-silica sol, 7 parts of sodium alginate solution, 4 parts of lanthanum chloride solution and 3 parts of nano-silicon dioxide.
[0079] The mass fraction of the sodium alginate solution in this embodiment is 6%; the mass fraction of the lanthanum chloride solution is 5%.
[0080] The preparation method of the chitosan modifier in this embodiment is:
[0081] S11: irradiating the yttrium oxide in a proton irradiation box for 10 minutes at an irradiation power of 400 W, and obtaining irradiated yttrium oxide after the irradiation is completed;
[0082] S12: 5 parts of irradiated yttrium oxide, 6 parts of chitosan solution, 3 parts of silane coupling agent KH550 and 2 parts of urea are mixed and ball-milled thoroughly at a ball-milling speed of 1500 r / min. After the ball-milling is completed, the mixture is filtered and dried to obtain a chitosan modifier.
[0083] The mass fraction of the chitosan solution in this embodiment is 5%.
[0084] This embodiment also provides a method for preparing a composite material for a shoe upper, comprising the following steps:
[0085] The raw materials were weighed according to their weight, and then styrene-butadiene rubber, butadiene rubber, EVA, edge adjustment functional bidirectional agent, chitosan modifier, zinc oxide, stearic acid and carbon black were first kneaded at a temperature of 175°C for 5 minutes, and then sulfur and vulcanization accelerator TMTM were added and kneaded at a temperature of 40°C for 45 minutes. After the kneading was completed, a composite material for shoe uppers was obtained.
[0086] Embodiment 3: A composite material for a shoe upper, comprising the following raw materials in parts by weight:
[0087] 40 parts of styrene-butadiene rubber, 37.5 parts of butadiene rubber, 12.5 parts of EVA, 11 parts of edge-adjusting functional bidirectional agent, 6.5 parts of chitosan modifier, 5 parts of zinc oxide, 3 parts of stearic acid, 3 parts of carbon black, 2.5 parts of sulfur, and 2.5 parts of vulcanization accelerator TMTM.
[0088] The preparation method of the bidirectional agent with side-modulating function in this embodiment is as follows:
[0089] S01: The nano-bentonite is first heat-treated at 310°C for 7.5 minutes, then cooled to 170°C at a rate of 3°C / min, kept warm for 5 minutes, and finally air-cooled to room temperature to obtain the heat-treated nano-bentonite;
[0090] S02: First prepare a phosphate buffer solution with a pH value of 5.2, then add 2 parts of silane coupling agent KH560 and 1.5 parts of sodium dodecylbenzene sulfonate solution to 5.5 parts of the phosphate buffer solution, and then add 3 parts of carboxymethyl cellulose and mix well to obtain a modified solution;
[0091] S03: stirring the heat-treated nano-bentonite and the modified liquid at a weight ratio of 2:5 for modification, washing with water and drying after the stirring is completed to obtain modified nano-bentonite;
[0092] S04: The modified nano-bentonite and the edge-adjusting agent are mixed and ball-milled in a weight ratio of 5:3 at a ball-milling speed of 1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain an edge-adjusting functional bidirectional agent.
[0093] The stirring speed of the stirring modification treatment in this embodiment is 600 r / min, and the stirring time is 25 min.
[0094] The mass fraction of the sodium dodecylbenzene sulfonate solution in this embodiment is 3.5%.
[0095] The side conditioning agent in this embodiment includes the following raw materials in parts by weight:
[0096] 3 parts of silicon carbide whiskers, 2 parts of nano-silica sol, 5.5 parts of sodium alginate solution, 3 parts of lanthanum chloride solution and 2 parts of nano-silicon dioxide.
[0097] The mass fraction of the sodium alginate solution in this embodiment is 5%; the mass fraction of the lanthanum chloride solution is 4%.
[0098] The preparation method of the chitosan modifier in this embodiment is:
[0099] S11: irradiating the yttrium oxide in a proton irradiation box for 7.5 minutes at an irradiation power of 375 W, and obtaining irradiated yttrium oxide after the irradiation is completed;
[0100] S12: 3.5 parts of irradiated yttrium oxide, 4.5 parts of chitosan solution, 2 parts of silane coupling agent KH550 and 1.5 parts of urea are mixed and ball-milled thoroughly at a ball-milling speed of 1250 r / min. After the ball-milling is completed, the mixture is filtered and dried to obtain a chitosan modifier.
[0101] The mass fraction of the chitosan solution in this embodiment is 3.5%.
[0102] This embodiment also provides a method for preparing a composite material for a shoe upper, comprising the following steps:
[0103] The raw materials were weighed according to their weight proportions, and then styrene-butadiene rubber, butadiene rubber, EVA, edge-adjusting functional bidirectional agent, chitosan modifier, zinc oxide, stearic acid and carbon black were kneaded at 170°C for 5 minutes, and then sulfur and vulcanization accelerator TMTM were added and kneaded at 40°C for 40 minutes. After the kneading was completed, a composite material for shoe uppers was obtained.
[0104] The temperature control range testing method of Examples 1-3 is as follows: the samples of Examples 1-3 to be tested are placed on a cold plate at 20°C in an incubator, taken out after 5 minutes, and the temperature of the tested samples is detected by a temperature sensor. The operation is repeated 5 times, and the average value is taken to obtain the lower limit of the temperature control; the test samples are placed on a hot plate at 35°C in an incubator, taken out after 5 minutes, and the temperature of the tested samples is detected by a temperature sensor. The operation is repeated 5 times, and the average value is taken to obtain the upper limit of the temperature control. The test results show that the temperature of Examples 1-3 is controlled in the range of 24-28°C.
[0105] Comparative Example 1:
[0106] The difference from Example 3 is that no bidirectional agent with side-adjusting function is added.
[0107] Comparative Example 2:
[0108] The difference from Example 3 is that S01 treatment was not used in the preparation of the edge-adjusting functional bidirectional agent.
[0109] Comparative Example 3:
[0110] The difference from Example 3 is that no modifying liquid treatment is used in the preparation of the edge-adjusting functional bidirectional agent.
[0111] Comparative Example 4:
[0112] The difference from Example 3 is that no side-adjusting agent treatment is used in the preparation of the side-adjusting functional bidirectional agent.
[0113] Comparative Example 5:
[0114] The difference from Example 3 is that no chitosan modifier is added.
[0115] Comparative Example 6:
[0116] The difference from Example 3 is that no irradiated yttrium oxide is added to the chitosan modifier.
[0117] Comparative Example 7:
[0118] The difference from Example 3 is that in the preparation of the chitosan modifier, the chitosan solution is replaced by deionized water and the silane coupling agent KH550 is not added.
[0119] The products of Examples 1-3 and Comparative Examples 1-7 were subjected to performance tests. The folding resistance of the products was tested with reference to GB / T 3903.1-2017 Test Method for Folding Resistance of Whole Shoes. The flexion angle was 50 degrees, the flexion number was 40,000 times, the flexion frequency was 230 times / minute, and the cut length was 5 mm. The test results are shown in Table 1.
[0120] Table 1 Product performance test results of Examples 1-3 and Comparative Examples 1-7:
[0121]
[0122] It can be seen from Comparative Examples 1 to 7 and Examples 1 to 3 that the product of Example 3 has excellent folding resistance, and also excellent abrasion resistance and water vapor transmittance performance, and the abrasion resistance, air permeability and folding resistance of the product can be improved in a coordinated manner;
[0123] From Comparative Examples 1 to 7 and Example 3, it can be seen that without adding either the bidirectional agent or the chitosan modifier, the performance of the product deteriorates significantly. The synergistic effect of the two is most obvious.
[0124] The performance of the products tended to deteriorate when S01 treatment, modifying liquid treatment and edge-adjusting agent treatment were not used in the preparation of the edge-adjusting functional bidirectional agent, and the irradiated yttrium oxide was not added to the chitosan modifier, deionized water was used instead of chitosan solution in the preparation of the chitosan modifier, and silane coupling agent KH550 was not added. The performance of the products tended to deteriorate when the edge-adjusting functional bidirectional agent and chitosan modifier obtained by different methods had a tendency to deteriorate. Only the product raw material obtained by the method of the present invention had the most significant product performance effect; and the performance of the product also showed a more obvious tendency to deteriorate when the edge-adjusting functional bidirectional agent was not treated with edge-adjusting agent in the preparation of the edge-adjusting functional bidirectional agent.
[0125] Based on the fact that side adjustments can significantly change product performance, further research is conducted on this.
[0126] Experimental Example 1:
[0127] The only difference from Example 3 is that no silicon carbide whiskers are added to the edge conditioning agent.
[0128] Experimental Example 2:
[0129] The only difference from Example 3 is that no lanthanum chloride solution is added to the side conditioning agent.
[0130] Experimental Example 3:
[0131] The only difference from Example 3 is that no nano silicon dioxide is added to the edge conditioning agent.
[0132] Experimental Example 4:
[0133] The only difference from Example 3 is that no nano silica sol is added to the edge conditioning agent.
[0134] Experimental Example 5:
[0135] The only difference from Example 3 is that no sodium alginate solution is added to the side conditioning agent.
[0136] The performance tests were performed on the products of Experimental Examples 1-5. The folding resistance of the products was tested with reference to GB / T 3903.1-2017 Test Method for Folding Resistance of Whole Shoes. The flexion angle was 50 degrees, the flexion number was 40,000 times, the flexion frequency was 230 times / minute, and the cut length was 5 mm. The test results are shown in Table 2.
[0137] Table 2 Product performance test results of Experimental Examples 1-5:
[0138]
[0139] It can be seen from Experimental Examples 1-5 that silicon carbide whiskers were not added to the edge adjuster. Among the preparation factors of the edge adjuster, the performance of the product deteriorated most significantly, followed by the absence of nano-silicon dioxide, and the absence of lanthanum chloride solution, nano-silica sol, and sodium alginate solution. The performance of the product showed a trend of deterioration. Only by using the specific raw materials of the present invention, the performance effect of the product was the most significant. Using other raw materials instead could not achieve the technical effect of the present invention.
[0140] The edge adjuster uses silicon carbide whiskers as the matrix, and combines silicon carbide whiskers with bentonite to improve the coordination of product performance, as well as blending nano-silica sol, sodium alginate solution, lanthanum chloride solution and nano-silicon dioxide. Through the coordination of high specific surface area nano-silicon dioxide and silicon carbide whiskers, it can synergistically improve the product's air permeability and wear resistance, optimize the product's folding stability and the product's excellent temperature control effect.
[0141] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0142] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A composite material for a shoe upper, characterized in that: It includes the following raw materials in parts by weight: 35-45 parts of styrene-butadiene rubber, 35-40 parts of butadiene rubber, 10-15 parts of EVA, 8-14 parts of edge-adjusting functional bidirectional agent, 5-8 parts of chitosan modifier, 4-6 parts of zinc oxide, 2-4 parts of stearic acid, 2-4 parts of carbon black, 2-3 parts of sulfur, 2-3 parts of vulcanization accelerator TMTM; The preparation method of the side-adjusting functional bidirectional agent is as follows: S01: The nano-bentonite is first heat-treated at 300-320°C for 5-10 minutes, then cooled to 170°C at a rate of 2-4°C / min, kept warm for 5 minutes, and finally air-cooled to room temperature to obtain the heat-treated nano-bentonite; S02: first prepare a phosphate buffer solution with a pH value of 5.0-5.5, then add 1-3 parts of silane coupling agent KH560 and 1-2 parts of sodium dodecylbenzene sulfonate solution to 4-7 parts of the phosphate buffer solution, and then add 2-4 parts of carboxymethyl cellulose and mix well to obtain a modified solution; S03: stirring the heat-treated nano-bentonite and the modified liquid at a weight ratio of 2:5 for modification, washing with water and drying after the stirring is completed to obtain modified nano-bentonite; S04: The modified nano-bentonite and the edge adjustment agent are mixed and ball-milled in a weight ratio of 5:3, the ball milling speed is 1500r / min, the ball milling is performed for 2h, and after the ball milling is completed, the mixture is washed with water and dried to obtain an edge adjustment functional bidirectional agent; The side adjustment agent includes the following raw materials in parts by weight: 2~4 parts of silicon carbide whiskers, 1~3 parts of nano-silica sol, 4~7 parts of sodium alginate solution, 2~4 parts of lanthanum chloride solution and 1~3 parts of nano-silicon dioxide; The preparation method of the chitosan modifier is: S11: irradiating the yttrium oxide in a proton irradiation box for 5-10 minutes at an irradiation power of 350-400W, and obtaining irradiated yttrium oxide after the irradiation is completed; S12: 2-5 parts of irradiated yttrium oxide, 3-6 parts of chitosan solution, 1-3 parts of silane coupling agent KH550 and 1-2 parts of urea are mixed and ball-milled thoroughly at a ball-milling speed of 1000-1500 r / min. After the ball-milling is completed, the mixture is filtered and dried to obtain a chitosan modifier.
2. A composite material for a shoe upper according to claim 1, characterized in that: The composite material for the upper comprises the following raw materials in parts by weight: 40 parts of styrene-butadiene rubber, 37.5 parts of butadiene rubber, 12.5 parts of EVA, 11 parts of edge-adjusting functional bidirectional agent, 6.5 parts of chitosan modifier, 5 parts of zinc oxide, 3 parts of stearic acid, 3 parts of carbon black, 2.5 parts of sulfur, and 2.5 parts of vulcanization accelerator TMTM.
3. The composite material for a shoe upper according to claim 1, characterized in that: The stirring speed of the stirring modification treatment is 550-750 r / min, and the stirring time is 20-30 min.
4. The composite material for a shoe upper according to claim 1, characterized in that: The mass fraction of the sodium dodecylbenzene sulfonate solution is 2-5%.
5. The composite material for a shoe upper according to claim 1, characterized in that: The mass fraction of the sodium alginate solution is 4-6%; the mass fraction of the lanthanum chloride solution is 3-5%.
6. The composite material for a shoe upper according to claim 1, characterized in that: The mass fraction of the chitosan solution is 2-5%.
7. A method for preparing a composite material for a shoe upper, used for preparing a composite material for a shoe upper as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: The raw materials are weighed according to weight, and then styrene-butadiene rubber, butadiene rubber, EVA, edge adjustment functional bidirectional agent, chitosan modifier, zinc oxide, stearic acid and carbon black are first kneaded at a temperature of 165-175°C for 5 minutes, and then sulfur and vulcanization accelerator TMTM are added and kneaded at a temperature of 40°C for 35-45 minutes. After the kneading is completed, a composite material for shoe uppers is obtained.
Citation Information
Patent Citations
Breathable sole and production process thereof
CN110607001A
Antibacterial composite material, preparation method and application of antibacterial composite material in sports shoes
CN118652484A